Pemimpin dan Feedback Rakyat di Indonesia Perspektif Al-Qur’an - Ayu Sugiarti; Muhammad Kudhori (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
Leadership in a state must have a shared role and responsibility between the ruler and the people in realizing peace in a nation. Even though the system used in Indonesia is democracy and the presidency, it must still maintain the sharia values contained in Islam. The purpose of preparing this paper is to find out the verses of the Koran relating to the relationship between leaders, the responsibility of leaders so that they have the value of justice, mutually beneficial responsibilities according to Islamic teachings. Likewise, the role of the community must take its position and provide feedback to the state. How to choose a leader who will be a determining figure in a country. The style used in writing papers is library or literature research using qualitative methods and referring to several journals, articles, books, books and websites that are related to the theme of discussion. With the primary source Al-Qur'an. So that we can find a conclusion about the relationship between the rulers and the people, namely giving them the responsibility to lead according to the verses of the Koran by maintaining human norms so that people must obey their leaders as long as they do not encourage evil.